2019
DOI: 10.1093/humrep/dez120
|View full text |Cite
|
Sign up to set email alerts
|

What is the prognosis for a live birth after unexplained recurrent implantation failure following IVF/ICSI?

Abstract: STUDY QUESTION What is the cumulative incidence of live birth and mean time to pregnancy (by conception after IVF/ICSI or natural conception) in women experiencing unexplained recurrent implantation failure (RIF) following IVF/ICSI treatment? SUMMARY ANSWER In 118 women who had experienced RIF, the reported cumulative incidence of live birth during a maximum of 5.5 years follow-up period was 49%, with a calculated median time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 29 publications
0
18
1
1
Order By: Relevance
“…Table 3 summarizes studies addressing live birth rates in patients with RIF in relation to the number of previous ART cycles who did not undergo LIT [18][19][20]. Although the live birth rates reported by Koot et al were significantly higher than those registered in our study (49% vs. 33%) [19], a comparison of these two analyses is limited by the following factors. First, 7 of 75 patients with RIF in our study (9%) were older than 39 years.…”
Section: Discussioncontrasting
confidence: 58%
“…Table 3 summarizes studies addressing live birth rates in patients with RIF in relation to the number of previous ART cycles who did not undergo LIT [18][19][20]. Although the live birth rates reported by Koot et al were significantly higher than those registered in our study (49% vs. 33%) [19], a comparison of these two analyses is limited by the following factors. First, 7 of 75 patients with RIF in our study (9%) were older than 39 years.…”
Section: Discussioncontrasting
confidence: 58%
“…Embryo implantation is a profound process composing of embryo apposition, adhesion, penetration, and invasion (Singh et al, 2011). Recurrent implantation failure (RIF) is defined as the absence of implantation after either transfer of three or more morphologically good quality embryos or placement of 10 or more embryos in several transfers (Koot et al, 2019). RIF has become an obstacle in assisted reproductive techniques and accounts for approximately 10% of women who fail to achieve a clinical pregnancy during their in vitro fertilization-embryo transfer (IVF-ET) treatment (Polanski et al, 2014;Macklon, 2017;Nowak et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, based on the results of this study, it seemed that it was inappropriate to include two implantation failure in the RIF definition. The date of RIF diagnosis was determined, defined as the first day of the menstrual period after the last failed IVF/ICSI/FET treatment ( 21 ). So, if a patient was under 40 years old and had failed to achieve a clinical pregnancy after transferring at least four cleavage embryos or two blastocysts, we could classify her at the second or third failed ET cycles (the hypothetical RIF definition: at least two failed ET cycles vs generally accepted RIF definition: at least three failed ET cycles).…”
Section: Discussionmentioning
confidence: 99%
“…But the other side of this results suggested that women’s fertility was damaged seriously and we should pay more attention to the biological age. A recent study of 118 women who had experienced RIF showed that the median pregnancy time was just 9 months after the diagnosis of RIF ( 21 ). And for RIF patients, the live birth rate decreased significantly with age.…”
Section: Discussionmentioning
confidence: 99%